Effects of the beta‐adrenergic receptor antagonist Propranolol on dyskinesia and L‐DOPA‐induced striatal DA efflux in the hemi‐parkinsonian rat. (27th April 2015) - Bhide, Nirmal; Lindenbach, David; Barnum, Christopher J.; George, Jessica A.; Surrena, Margaret A.; Bishop, Christopher
Abstract Dopamine (DA) replacement therapy with L‐DOPA continues to be the primary treatment of Parkinson's disease; however, long‐term therapy is accompanied by L‐DOPA‐induced dyskinesias (LID). Several experimental and clinical studies have established that Propranolol, a β‐adrenergic receptor antagonist, reduces LID without affecting L‐DOPA's efficacy. However, the exact mechanisms underlying these effects remain to be elucidated. The aim of this study was to evaluate the anti‐dyskinetic profile of Propranolol against a panel of DA replacement strategies, as well as elucidate the underlying neurochemical mechanisms. Results indicated that Propranolol, in a dose‐dependent manner, reduced LID, without affecting motor performance. Propranolol failed to alter dyskinesia produced by the D1 receptor agonist, SKF81297 (0.08 mg/kg, sc), or the D2 receptor agonist, Quinpirole (0.05 mg/kg, sc). These findings suggested a pre‐synaptic mechanism for Propranolol's anti‐dyskinetic effects, possibly through modulating L‐DOPA‐mediated DA efflux. To evaluate this possibility, microdialysis studies were carried out in the DA‐lesioned striatum of dyskinetic rats and results indicated that co‐administration of Propranolol (20 mg/kg, ip) was able to attenuate L‐DOPA‐ (6 mg/kg, sc) induced DA efflux. Therefore, Propranolol's anti‐dyskinetic properties appear to be mediated via attenuation of L‐DOPA‐induced extraphysiological efflux of DA. We investigated the ability of the beta‐adrenergic receptor (βAR) antagonist Propranolol to reduce drug‐induced dyskinesia in hemi‐parkinsonian rats. Dyskinesia induced by L‐3, 4‐dihydroxyphenylalanine (L‐DOPA), but not D1 or D2 agonists was reduced by Propranolol. In vivo striatal microdialysis revealed that Propranolol's anti‐dyskinetic effects were related to an attenuation of L‐DOPA‐induced dopamine (DA) efflux. These findings show that pre‐synaptic βAR mediate L‐DOPA‐induced dyskinesia (LID) and highlight Propranolol's therapeutic potential.